Empire and identity in Guizhou : local resistance to Qing expansion - Weinstein, Jodi L. (Studies on ethnic groups in China., 2013)
"This historical investigation describes the Qing imperial authorities' attempts to consolidate control over the Zhongjia, a non-Han population, in eighteenth-century Guizhou, a poor, remote, and environmentally harsh province in Southwest China. Far from submitting peaceably to the state's quest for hegemony, the locals clung steadfastly to livelihood choices--chiefly illegal activities such as robbery, raiding, and banditry--that had played an integral role in their cultural and economic survival. Using archival materials, Indigenous folk narratives, and ethnographic research, Jodi L. Weinstein shows how these seemingly subordinate populations challenged state power. Jodi L. Weinstein teaches history at The College of New Jersey"--